2019
DOI: 10.1016/j.energy.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of elevated temperature CO2 adsorbents from aqueous miscible organic-layered double hydroxides

Abstract: Layered double oxides (LDOs), which derives from the calcination of layered double hydroxides (LDHs), are a type of elevated temperature CO2 adsorbents for precombustion carbon capture. Due to its highly aggregated stone-like structure, the CO2 capture capacity of commercial MgAl-CO3 LDO is relatively low. A novel method, the aqueous miscible organic solvent treatment (AMOST), was proposed to synthesize LDH precursors with increased surface area. In this work, three types of LDHs and LDOs with different Mg/Al … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Similarly, the X-ray absorption near-edge structure (XANES) at the Ir L 3 -edge of Ir-NiO (Figure c) shows that the white line peak position is around the same position compared to IrO 2 , suggesting the oxidation state of Ir in Ir-NiO is very close to 4+, , which is consistent with the XPS finding. In addition, the white line intensity is in principle proportional to the d orbital density of states that are affected by the presence of multiple oxidization states and different electron configurations. The higher white line indicates more empty d orbital states compared to IrO 2 and thus less electron density. The Ni oxidization state is slightly higher than NiO after Ir doping (Figure d), which has the same trend as that of XPS.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the X-ray absorption near-edge structure (XANES) at the Ir L 3 -edge of Ir-NiO (Figure c) shows that the white line peak position is around the same position compared to IrO 2 , suggesting the oxidation state of Ir in Ir-NiO is very close to 4+, , which is consistent with the XPS finding. In addition, the white line intensity is in principle proportional to the d orbital density of states that are affected by the presence of multiple oxidization states and different electron configurations. The higher white line indicates more empty d orbital states compared to IrO 2 and thus less electron density. The Ni oxidization state is slightly higher than NiO after Ir doping (Figure d), which has the same trend as that of XPS.…”
Section: Resultsmentioning
confidence: 99%
“…This method has been frequently utilized to enhance specific surface area of pristine itself [ 60 ]. Zhu et al [ 61 ] prepared LDH through conventional coprecipitation and washed the slurry with acetone (purchased from Sigma-Aldrich Inc., St. Louis, MO, USA). Upon rinsing with acetone, the interlayer water was removed and the interaction between the LDH sheets was weakened, resulting in the exfoliation.…”
Section: Specific Surface Area Of Mmo Prepared From Calcined Ldhmentioning
confidence: 99%
“… The schematic diagram of synthesis of AMOS-LDH and AMOS-MMO (adapted [ 61 ] with permission from Elsevier, 2019). …”
Section: Figures Scheme and Tablesmentioning
confidence: 99%
“…In contrast, the CO 2 adsorption capability of Mg 3 Al-CO 3 SLDH is 0.9 mmol g −1 , four times higher than that of struvite, 74% of this capacity is due to physisorption, which is ascribed to high specific surface area and large pore volume, whilst 26% is chemisorption that is ascribed to the presence of moderate basic sites in the SLDO. 28,30 In summary, we have shown that struvite (including waste water treatment plant samples) can be both an efficient, green source of magnesium and phosphate and create a structural scaffold for the preparation of a new class of dense porous Mg n Al-A SLDHs (n = 2, 3; A = CO 3 , PO 4 ). Our preliminary studies suggest the transformation proceeds via a dissolutioncrystallisation mechanism; possesses high surface area, large pore volume and high tap densities, a combination not found in conventional LDHs and AMO-LDHs.…”
mentioning
confidence: 92%